2020
DOI: 10.1101/2020.11.02.20224212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review and meta-analysis of evidence on the efficacy of e-cigarette use for sustained smoking and nicotine cessation

Abstract: Objective: To systematically review and meta-analyse evidence regarding the efficacy of electronic nicotine delivery systems (ENDS) as smoking cessation aids. Data Sources: PubMed, Scopus, Web of Science, PsycINFO, MEDLINE and Cochrane Library were searched up to February-March 2020 (PROSPERO registration CRD42020170692). Study selection: Published peer-reviewed randomised controlled trials (RCTs) of the efficacy of ENDS for sustained cessation of combustible tobacco smoking and/or nicotine use, compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 63 publications
1
44
0
1
Order By: Relevance
“…Systematic review and meta-analysis found that nicotine containing Ecigarette provide more efficacy for smoking cessation when compared with nicotine-free E-cigarette and nicotine replacement therapy [24,25]. Another report found that there was not sufficient support for E-cigarette for smoking cessation [26]. In contrast to previous reports, Kalkhoran et al found that the odds of quitting cigarette in E-cigarette user was 28% lower than those who did not use E-cigarette [27].…”
Section: Discussionmentioning
confidence: 91%
“…Systematic review and meta-analysis found that nicotine containing Ecigarette provide more efficacy for smoking cessation when compared with nicotine-free E-cigarette and nicotine replacement therapy [24,25]. Another report found that there was not sufficient support for E-cigarette for smoking cessation [26]. In contrast to previous reports, Kalkhoran et al found that the odds of quitting cigarette in E-cigarette user was 28% lower than those who did not use E-cigarette [27].…”
Section: Discussionmentioning
confidence: 91%
“…There continues to be some debate regarding the safety of NVPs with data suggesting they are harmful products coming from predominantly in vitro studies or clinical case studies reporting small numbers of burns, suspected acute lung injury or acute nicotine toxicity. [50] There is no evidence linking e-cigarettes to the highest burden diseases caused by or linked to tobacco smoking including cardiovascular disease, cancer, respiratory conditions, mental health, development in children and adolescents, reproduction, sleep, wound healing, neurological conditions other than seizures, and endocrine, olfactory, optical, allergic and haematological conditions. [50] Furthermore, all randomised controlled trials of NVPs have failed to identify safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…[50] There is no evidence linking e-cigarettes to the highest burden diseases caused by or linked to tobacco smoking including cardiovascular disease, cancer, respiratory conditions, mental health, development in children and adolescents, reproduction, sleep, wound healing, neurological conditions other than seizures, and endocrine, olfactory, optical, allergic and haematological conditions. [50] Furthermore, all randomised controlled trials of NVPs have failed to identify safety issues. [25] Although not a safety trial, this trial will add to the evidence base of the safety of NVPs with reporting of adverse events in an otherwise high morbidity group.…”
Section: Discussionmentioning
confidence: 99%
“… Villanti et al (2018) demonstrated that e-cigarettes could be used to decrease cigarette use; however, this review only included a limited number of studies, and most were not randomized control trials (RCTs) ( Villanti et al, 2018 ). Banks et al (2020) concluded that there is insufficient evidence to support the efficacy of electronic nicotine delivery systems (ENDS) (vs. no intervention) for smoking cessation ( Banks et al, 2020 ). They also noted the quality of the evidence was low and the consideration of studies with no potential competing interest further limits the evidence ( Banks et al, 2020 ).…”
Section: Is Vaping a Viable Smoking Cessation Aid?mentioning
confidence: 99%
“… Banks et al (2020) concluded that there is insufficient evidence to support the efficacy of electronic nicotine delivery systems (ENDS) (vs. no intervention) for smoking cessation ( Banks et al, 2020 ). They also noted the quality of the evidence was low and the consideration of studies with no potential competing interest further limits the evidence ( Banks et al, 2020 ).…”
Section: Is Vaping a Viable Smoking Cessation Aid?mentioning
confidence: 99%